Mobile health-based home rehabilitation education improving early outcomes after anterior cruciate ligament reconstruction: A randomized controlled clinical trial - Guo, Yi; Li, Dai; Wu, Yi-bo; Sun, Xin; Sun, Xin-ying; Yang, Yu-ping (Frontiers in Public Health, 2023)
Objective This study aimed to assess changes in joint range of motion (ROM) and knee joint function between patients who received the mobile health-based intervention and those who received regular care at 2 and 6 weeks after anterior cruciate ligament (ACL) reconstruction to provide better interventions in the future. Methods Patients who underwent ACL reconstruction were randomized into the experimental [Mobile health-based intervention (MHI); n = 62] and control (CON) groups (n = 63). The CON group underwent home-based rehabilitation exercise following the paper rehabilitation schedule, while the intervention group received additional mobile health-based education at weeks 1–6 after surgery. ROM, thigh circumference difference, and flexion pain were the primary outcomes. The secondary outcomes were the international knee documentation committee knee evaluation form (IKDC) scores and rehabilitation compliance scores. All the outcomes were measured 1 day before surgery as references and at 2 and 6 weeks after surgery. Results There was no statistical difference in the patients' ROM, thigh circumference difference, and VAS scores at the 2-week follow-up. At the 6-week follow-up, the ROM of the affected leg was (118.1 ± 20.5)° in the CON group and (126.6 ± 20.5)° in the MHI group, and the difference was statistically significant (P = 0.011). The difference in thigh circumference was 3.0 (2.0, 3.5) cm in the CON group and 2.5 (1.0, 3.0) cm in the MHI group. The difference was statistically significant (P < 0.001). The VAS score in the CON group was 3.0 (2.0, 4.0), and the MHI group was 2.5 (1.0, 3.0). The difference was statistically significant (P < 0.05). At the 6-week follow-up, the compliance score of patients in the MHI group was significantly higher than that in the CON group (P = 0.047, β = 2.243, 95%CI: 0.026–4.459). There is no statistically significant difference in IKDC scores. Conclusion Mobile health-based intervention positively affected patients undergoing ACL reconstruction surgery, particularly in improving the clinical outcome indicators of the knee joint.